Management and outcomes of pregnant patients with central nervous system hemangioblastoma. (November 2018) - Ma, Xiu-jian; Zhang, Guo-bin; Guo, Teng-xian; Li, Cheng-bei; Chen, Yu-jia; Zhang, Li-wei; Wu, Zhen; Zhang, Jun-ting
Highlights: Reciprocal effects between pregnancy and hemangioblastomas were not thoroughly clear. Symptomatic treatment was the first choice for these patients, especially for those with spinal hemangioblastoma. Safe urgent tumor resection was possible with careful maternal and fetal monitoring if necessary. Both maternal and born fetal prognoses were favorable in the long run. Abstract: The study aims to assess the management and maternal and fetal outcomes of pregnancies complicated by central nervous system (CNS) hemangioblastoma. Twenty-four female patients with CNS hemangioblastoma, who were pregnant in a tumor-burden status, were identified. Their medical charts, treatments, and follow-up materials were carefully reviewed. Of the included 24 CNS patients with hemangioblastoma (14 intracranial and 10 spinal hemangioblastomas), 5 patients (20.8%) were diagnosed with Von Hippel-Lindau disease (VHL). The median age of these patients at admission was 27.5 years. Intracranial hypertension was a common presenting symptom for patients with intracranial hemangioblastoma and was observed in 85.7% (12/14) of cases; the other 10 patients with spinal hemangioblastomas all suffered from paresthesia. Overall, 66.7% (16/24) of patients with CNS hemangioblastoma went through the gestational course with conventional observation; 16.6% (4/24) of patients accepted a ventriculo-peritoneal shunt (VPS) to delay the tumor resection; and 16.7% (4/24) of patients needed urgent tumor resection even when symptomatic treatments were given. Variable symptom improvement was seen when patients had follow-up visits at a median of 32.5 months. No maternal death or tumor recurrence was identified. For the fetal prognoses, one (4.2%) pregnancy ended in a spontaneous miscarriage and for (16.7%) pregnancies were interrupted; the other 19 (79.2%) live births were in good status without any congenital malformations. Symptomatic treatment was the first choice for pregnant patients with CNS hemangioblastoma. When needed, urgent tumor resection could be safely achieved with careful maternal and fetal monitoring. Both maternal and fetal prognoses were favorable during follow-up.